2018
DOI: 10.4102/phcfm.v10i1.1633
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nurses’ cardiopulmonary resuscitation knowledge and skills within three district hospitals in Botswana

Abstract: BackgroundNurses are usually the first to identify the need for and initiate cardiopulmonary resuscitation (CPR) on patients with cardiopulmonary arrest in the hospital setting. Cardiopulmonary resuscitation has been shown to reduce in-hospital deaths when received from adequately trained health care professionals.AimWe aimed to investigate nurses’ retention of CPR knowledge and skills at district hospitals in Botswana.MethodsA quantitative, quasi-experimental study was conducted at three hospitals in Botswana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1
4

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 24 publications
1
44
1
4
Order By: Relevance
“…Since then, some other studies have been published, including a cut-off score. Saramma et al [33] and Rajeswaran et al [34] calculated the overall performance based on an average of a post-training knowledge score, and a score of 70% was set as a pass mark for overall performance. Others used steps in skills assessment that were graded and assigned penalty points, based on the participants' levels of performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, some other studies have been published, including a cut-off score. Saramma et al [33] and Rajeswaran et al [34] calculated the overall performance based on an average of a post-training knowledge score, and a score of 70% was set as a pass mark for overall performance. Others used steps in skills assessment that were graded and assigned penalty points, based on the participants' levels of performance.…”
Section: Discussionmentioning
confidence: 99%
“…Others used steps in skills assessment that were graded and assigned penalty points, based on the participants' levels of performance. [34,35] To evaluate the impact of a formal certified CPR training program on the knowledge and skill of CPR among nurses, we have used, in this study, a cut-off score according to the International Liaison Committee on Resuscitation (ILCOR) recommendations. [7] In those guidelines, a more rigorous evaluation for a specific group (health workers, first responders and instructors) was demanded; the current recommendations focus on the teaching of high-quality CPR.…”
Section: Discussionmentioning
confidence: 99%
“…The study was also limited by testing participants before and soon after the PowerPoint training intervention, and it is not known whether there was retention of knowledge in the longer term -this requires further investigation. There is much argument about performing the post test immediately after any PowerPoint training intervention; [36,37] however, this immediate post-test was a practical solution owing to time constraints and the logistical problems of sampling the same staff members again for post tests after a month in an environment of shift work. In the present study, no attrition of participants occurred in the post test that was applied immediately after the PowerPoint training intervention, in contrast to a Botswana nursing study [37] that concluded a reduction in participants from 154 to 85 in a post test 6-months after the initial test.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Open access respiratory technology in RLS is the presence of a highquality training programme. 5 Current data suggest that knowledge and skills retention after initial training programmes decline over time, [6][7][8][9][10][11] highlighting the need for ongoing refresher training in order to sustain competency. As part of the initial deployment of high flow in the paediatric intensive care unit (PICU) at Instituto Nacional de Salud del Niño (INSN) in 2016, we developed a comprehensive multidisciplinary high flow training programme that included initial and refresher training sessions for all PICU staff.…”
Section: Introductionmentioning
confidence: 99%